Pengaruh Likuiditas dan Leverage terhadap Agresivitas Pajak (Studi Kasus pada Perusahaan Sektor Pertambangan di Bursa Efek Indonesia (BEI) Periode 2018-2022) - Mourine Andika Putri; Tartila Devy (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to investigate the effect of Liquidity and Leverage on Tax Aggressiveness in mining sector companies listed on the Jakarta Islamic Index 70 (JII-70) during the period 2018-2022. The research method used is a quantitative method using financial data from these companies. The study population consisted of 70 companies, with a sample of 27 companies selected using purposive sampling method. Data analysis was carried out using descriptive statistical analysis, classical assumption test, and multiple linear regression analysis with the help of the IBM SPSS 26 application. The variables tested include Tax Aggressiveness (ETR) as the dependent variable, as well as Liquidity (CR) and Leverage (DER) as independent variables. The results showed that partially, Liquidity did not have a significant effect on tax aggressiveness, with a significance value above 0.05 (0.158> 0.05). On the other hand, Leverage partially affects tax aggressiveness significantly, with a significance value below 0.05 (0.000 < 0.05). Together, Liquidity and Leverage have a significant influence on tax aggressiveness, with a significance value below 0.05 (0.002 < 0.05) and an f_count value of 6.749 > f_(table) 3.06. In addition, the R^2 analysis shows that Liquidity and Leverage together affect Tax Aggressiveness by 18.2%, while 81.1% is influenced by other factors not examined in this study.